Géorgie-Ossétie-Russie. Une guerre à toutes les échelles - Julien Thorez (EchoGéo)
In August 2008, after the war against Georgia, Russia decided to recognize the sovereignty of the secessionist Georgian regions of Abkhazia and south Ossetia, which are de facto independent since the early 1990’s. This war, unleashed by the action of he Georgian president M. Saakashvili, was a consequence of a clash between contrasting geopolitical goals in Caucasus. This article adopts a multi-scale approach to explain the war, analyzing its various dimensions, starting with the Abkhazian and Ossetian separatisms and the Georgian policy, aimed at “unifying” and modernizing the country, but dealing as well with the complex relationship between Russia and Georgia and finally with the wider international geopolitical rivalries playing out in the Caucasus.